2017
DOI: 10.1111/jmwh.12600
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction With Maternity Waiting Homes in Liberia: A Case Study During the Ebola Outbreak

Abstract: This case study demonstrated that women using MWHs in Bong County, Liberia are generally satisfied with their experience and plan to use an MWH again during future pregnancies to access a skilled birth attendant for birth. Women are also willing to encourage family and friends to use MWHs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Such sessions could also improve the quality of the experience at the MWH by providing a close bond among the MWH users and also among the staff and the MWH users. A qualitative study of MWH users in Liberia found that women valued a restful and supportive environment and that loneliness can be an issue at the time of delivery [ 22 ]. A review of the determinants of satisfaction with maternal health services in low and middle income countries, indicated that women value information and counseling from providers [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such sessions could also improve the quality of the experience at the MWH by providing a close bond among the MWH users and also among the staff and the MWH users. A qualitative study of MWH users in Liberia found that women valued a restful and supportive environment and that loneliness can be an issue at the time of delivery [ 22 ]. A review of the determinants of satisfaction with maternal health services in low and middle income countries, indicated that women value information and counseling from providers [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lori et al state that traditional birth attendants have taken responsibility for the cleaning of the MWHs as well as to support the pregnant women. 13 In another study, Lori et al found that births increased and maternal mortality decreased in communities with MWHs that employed both skilled and traditional birth attendants compared to communities without such MWHs. 22 This approach is worth testing in other low-income countries, such as Ethiopia, to bridge the cultural gap between the community and the MWH/facility.…”
Section: Plan-do-check-actmentioning
confidence: 98%
“…10 Interventions with a proven significant impact on maternal and newborn survival in low-and middle-income countries include family planning, management of unwanted pregnancies, provision of focused antenatal care, active management of the third stage of labor, neonatal resuscitation with bag and mask, and immediate thermal care. 11 The studies by Vian et al 12 and Lori et al 13 in this issue of the Journal concern maternity waiting homes (MWHs). This intervention has the potential to contribute toward reducing maternal and perinatal deaths, but only when implemented within a broader structure aimed at improving maternal and neonatal outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Responders arrived on the ground to scarce resources and historically rooted political instabilities that strained their best efforts. Communities questioned the trustworthiness of government messaging surrounding Ebola transmission 6–10. Healthcare workers themselves lost trust in the safety of their workplace as coworkers died 6.…”
Section: Introduction: Trust As a Social Technologymentioning
confidence: 99%